Análise do efeito do regulador transcricional TagK na regulação do sistema de secreção do tipo VI de Xanthomonas citri subsp. citri : Analysis of the effect of the transcriptional regulator TagK on the regulation of the type VI secretion system of Xanthomonas citri subsp. citri - Santana, Eliane Silva de, 1990- (2021)
Orientador: Cristina Elisa Alvarez Martinez